First Steps on the Quality Journey - O’Connor, Tony; Hinds, Sean (The International Hydrographic Review, 2002)
The Canadian Hydrographic Service (CHS) prides itself on its paramount attention to quality. CHS hydrographers and cartographers have long held the banner of ‘quality’ as the ‘flagship of service’. The dramatic revolution in technology, client demands and organisational culture has shaken the historic pillars of quality assurance in CHS. In response, CHS is moving to reinforce this foundation of quality with a new business model anchored by the culture of a Quality Management System. This paper will reflect on the changed environment that faces CHS and the quality lessons in the global marketplace that can be applied to a hydrographic organisation. It will explore the first steps that CHS has taken on this journey as it moves toward the goal of becoming an ISO 9000 certified ‘quality-organisation’.